A royal affair = En kongelig affære / [videorecording [(DVD)] - Arcel, Nikolaj; Arcel, Nikolaj; Vikander, Alicia, 1988-; Mikkelsen, Mads, 1965-; Følsgaard, Mikkel Boe; Dyrholm, Trine, 1972-; Dencik, David, 1974-; Walter, Harriet; Steensen-Leth, Bodil, 1945- (Magnolia Home Entertainment, 2013)
The passionate and forbidden romance between the mad Danish King, the royal physician, and the young but strong-willed Queen leads to a revolution that changes an entire nation.